Electron beam generation by electron multiplication - Szapiro, B., author; Murray, C., author; Rocca, Jorge J., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1989)
We have demonstrated that intense pulsed electron beams can be created by multiplication of lower current electron streams impinging on a high electron yield target. A 17 A electron beam of 1 μs pulse width was generated from a 2.5 A beam bombarding an activated Ag-Mg target 2.5 cm in diameter.